Integration Analysis of the International Sharia Stock Price Index to the Jakarta Islamic Index 2018-2022 Period - Citra Pratiwi Daulay, Suci; Soemitra, Andri; Arif Lubis, Fauzi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of this study is to determine the relationship between the Malaysia Shariah Gold Index (FTFBMS) and the Jakarta Islamic Index, the relationship between the Dow Jones Islamic Market Index Japan (DJIJP) and the Jakarta Islamic Index, the relationship between the Dow Jones Islamic Market Index Europe (DJIEU) and Jakarta Islamic Index, Relationship between the US Dow Jones Islamic Market Index (IMUS) and the Jakarta Islamic Index. The research method used in this research is secondary quantitative by taking weekly time series data for the period 2018-2022, the data sources used are from the websites www.investing.com and www.idx.com. This research uses vector autoregressive analysis with the Eviews 12sv application. The results of the research are: The short-term VECM estimation results show that in fact there is a significant short-term relationship of the variables that affect JII, namely DJIJP because it has a t count value that is greater than the t table. The short-term VECM estimation results show that in fact there is a significant short-term relationship of several variables that affect FTFBMS, namely the FTFBMS itself, and DJIEU because it has a calculated t value that is greater than t table. The results of the short-term VECM estimation show that in fact there is a significant short-term relationship of several variables that affect DJIJP, namely DJIJP itself, JII, DJIEU, and IMUS because they have a calculated t value that is greater than t table. The short-term VECM estimation results show that in fact there is a significant short-term relationship of the variables that affect DJIEU, namely JII and IMUS because they have a tcount value that is greater than t table. The short-term VECM estimation results show that there is no significant short-term relationship with the IMUS variable.